Land drainage and flood defence responsibilities (ICE Publishing, 2016)
This book offers practical, engineering-focused coverage of the legislation relating to water management, flood risk and drainage. Owing to increasingly erratic weather patterns and the effects of climate change, the topics of drainage and flood are becoming ever more important for policymakers and the engineers and construction professionals charged with responding to these changes. This Fifth Edition has been fully updated to reflect the significant changes which have been made to both domestic and European legislation since the last edition was published in 2010. Each chapter now includes separate sections outlining any differences in legislation between England, Scotland, Wales and Northern Ireland. This book is essential reading for engineers, consultants and design/construction professionals working within the water industry, particularly in sectors relating to flooding and drainage operations.